Perception of Stigma and Its Associated Factors Among Patients With Major Depressive Disorder: A Multicenter Survey From an Asian Population - Sun, Yan; Chen, Gang; Wang, Li; Li, Nan; Srisurapanont, Manit; Hong, Jin Pyo; Hatim, Ahmad; Chen, Chia-hui; Udomratn, Pichet; Bae, Jae Nam; Fang, Yi-Ru; Chua, Hong Choon; et al. (Frontiers in Psychiatry, 2019)
Stigma of major depressive disorder (MDD) is an important public health problem. This study aimed to examine the level of perceived stigma and its associated factors in MDD patients in 5 Asian countries, including China, Korea, Malaysia, Singapore and Thailand. A total of 547 outpatients with MDD were included from Asian countries. We used the stigma scale of the Explanatory Model Interview Catalogue (EMIC) to assess stigma. Montgomery-Asberg Depression Rating Scale (MADRS), Symptoms Checklist 90-Revised (SCL-90R), Fatigue Severity Scale (FSS), Sheehan Disability Scale (SDS), 36-Item Short-Form Health Survey (SF-36), and Multidimensional Scale of Perceived Social Support (MSPSS) were used to assess symptoms, clinical features, functional impairment, health status and social support. The stigma scores of patients under 55 years old were significantly higher than those of equal or greater than 55 years old of age (P < 0.001). The stigma scores exhibited significant negative correlation with age, MSPSS scores of family, friends and others, SF-36 subscale of mental health, but significant positive correlation with MADRS, FSS, SDS and SCL-90R subscale scores of depression, interpersonal sensitivity, obsession-compulsion, psychoticism and somatization. Multivariate regression analysis revealed that age, SCL-90R interpersonal sensitivity, obsession-compulsion, and psychoticism, MSPSS scores of friends and others, and SF-36 of mental health were significantly associated with the level of perceived stigma. These findings suggest that MDD patients who are young, have a high degree of interpersonal sensitivity and psychoticism, have low health-related quality of life, and have low social support are the target population for stigma interventions in Asia.